A Microchannel‐Confined Crystallization Strategy Enables Blade Coating of Perovskite Single Crystal Arrays for Device Integration. Issue 16 (4th March 2020) - Deng, Wei; Jie, Jiansheng; Xu, Xiuzhen; Xiao, Yanling; Lu, Bei; Zhang, Xiujuan; Zhang, Xiaohong
Abstract: Perovskite single crystals (PSCs) possess superior optoelectronic properties compared to their corresponding polycrystalline films, but their applications of PSCs in high‐performance, integrated devices are hindered by their heavy thickness and difficulty in scalable deposition. Here, a microchannel‐confined crystallization (MCC) strategy to grow uniform and large‐area PSC arrays for integrated device applications is reported. Benefiting from the confinement effect of the microchannels, solution flow dynamics is well controlled, and thus uniform deposition of PSC arrays with suitable thickness is achieved, meaning they are applicable for scale‐up device applications. The resulting PSCs possess excellent optoelectronic properties in terms of a long carrier lifetime (175 ns) and an ultralow defect density (2 × 10 9 cm −3 ), which are comparable to the corresponding bulk crystals. The unique embedded structure of PSCs within the microchannels allows the construction of a high‐integration image sensor. This work paves the way toward high‐throughput growth of PSCs for integrated optoelectronic devices. Abstract : A microchannel‐confined crystallization (MCC) strategy is proposed for scalable deposition of high‐quality perovskite single crystal (PSC) arrays through blade coating. The resultant PSC arrays exhibit perfect single‐crystalline nature and possess excellent optoelectronic properties. An image sensor based on the PSC arrays demonstrates a high‐sensitivity and high‐resolution imaging capability with a broad linear dynamic range and a large detectivity.